The comparative study of first and final year nursing students on depression, anxiety and stress towards death and dying / Norasmani Aluwi, Nurain Shahira Mukhtar and Rosmira Hafizah Sulong - Aluwi, Norasmani; Mukhtar, Nurain Shahira; Sulong, Rosmira Hafizah (Faculty of Health Sciences, 2015)
BACKGROUND: Everyone will face death and dying, whether their own family members or other people. However, nursing students are more exposed to encounter death and dying during their practice session. This experience will produce negative emotional state such depression, anxiety and stress on the individual. Therefore, the aims of this study is to determine depression, anxiety and stress between first and final year nursing students towards death and dying and to compare the first and final year nursing students' depression, anxiety and stress with demographics. METHODS: A universal sampling of first and final year nursing students UiTM Puncak Alam were approached and recruited to answer the questionnaire. There were 89 respondents who completed the demographic questionnaire and negative emotional states: depression, anxiety and stress. RESULTS: Results showed significant difference between first and final year nursing students on the level of depression p=0.013, anxiety p=0.002 and stress p=0.008. The significant differences were between levels of depression, anxiety and stress with age (p< 0.001). Gender was found to be significantly different with anxiety level of final year nursing students (p=0.02). . CONCLUSIONS: In conclusion, level of depression, anxiety and stress of first year nursing students were higher as compared to final year nursing students. Furthermore, there was a significant difference between first and final year nursing students on depression, anxiety and stress with age. Findings also revealed there was a significant difference gender with level of depression while final year students with level of anxiety. Therefore, it is important to understand the experience of nursing students facing death and dying because the quality of nursing care can be affected when student nurses experiences depression, anxiety and stress. The findings of this research can be used to develop recommendations for nursing student improvement in their ability to face death and dying.